The Impact of an Educational Program on ICU Nurses' Eye Care Knowledge and Practices - Gholamnejad, Hanieh; Moosavi, Soolmaz; Ghofrani Kelishami, Fatemeh; Haghani, Shima (Advances in Nursing & Midwifery, 2023)
Introduction: The majority of ICU patients require holistic care, neglecting which can lead to various issues, including eye-related problems. This research aimed to assess the impact of a designed educational program focusing on eye care for patients on the knowledge and practice of ICU nurses in selected hospitals affiliated with Iran University of Medical Sciences. Methods: A semi-experimental study investigated the impact of a designed educational program on the knowledge and performance of 126 nurses working in the ICU departments in Tehran during the year 1402. The intervention consisted of three 2-hour educational sessions. The control group received standard hospital training. Data analysis utilized descriptive and analytical statistics, chi-square, independent t-tests, and paired t-tests with SPSS version 19 software. To adhere to research ethics, educational booklets were also provided to the nurses in the control group after the sessions. Results: Initially, there were no statistically significant demographic differences between the groups. Pre-intervention, both control and intervention groups exhibited similar average scores in knowledge and practice. However, following the training sessions, the intervention group's scores notably improved, leading to a statistically significant difference between the two groups (knowledge P= 0.000 and practice = P= 0.02). Conclusions: Training on eye care proves effective in enhancing nurses' knowledge and skills. It appears essential to incorporate workshops and ongoing training sessions for sustained improvement and optimal outcomes. In this way, it is possible to prevent eye problems in patients hospitalized in ICUs, and if they occur, timely care can achieve favorable results.